Is there an association between immunosuppressant therapy medication adherence and depression, quality of life, and personality traits in the kidney and liver transplant population? - Gorevski E; Succop P; Sachdeva J; Cavanaugh TM; Volek P; Heaton P; Chisholm-Burns M; Martin-Boone JE (Patient Preference and Adherence, 2013)
Elizabeth Gorevski,1 Paul Succop,1 Jyoti Sachdeva,1 Teresa M Cavanaugh,1 Paul Volek,1 Pamela Heaton,1 Marie Chisholm-Burns,2 Jill E Martin-Boone1 1University of Cincinnati, Cincinnati, OH, USA, 2University of Tennessee College of Pharmacy, Memphis, TN, USA Objectives: To measure the association of transplant patients' personality, depression, and quality of life with medication adherence in kidney and liver transplant recipients. Methods: A cross-sectional study of liver and kidney transplant recipients greater than 1 year post-transplant was conducted. Patients’ adherence with medications was assessed using the Immunosuppressive Therapy Adherence Scale. Personality and depression were assessed using the NEO Five-Factor Inventory Scale and Patient Health Questionnaire 9, respectively. Quality of life was assessed using the Short Form-36, and functional status was determined using the Karnofsky Performance Status Scale. Results: A total of 86 kidney and 50 liver transplant patients completed the surveys. Logistic regression analysis demonstrated an association between depression and adherence with immunosuppressive medications in kidney transplant recipients. Kidney transplant patients who exhibited “low openness” scores were 91% more likely to be nonadherent. Kidney transplant patients’ physical functional status was strongly associated with nonadherence, and for each point increase in functionality the patients adherence increased by 4%. In the liver sample, age was associated with adherence. For every year increase in age, adherence increased by 7%. Conclusion: The presence of low openness as a personality trait, poor physical functional status, and depression were associated with adherence in the kidney transplant population. In the liver transplant population, younger age was associated with nonadherence. Keywords: adherence, transplant, liver, kidney